Prinsip Itikad Baik dalam Hubungan Industrial antara Manajemen dan Serikat Pekerja Hero Supermarket (SPHS) - Astuti Ayu Wulan (Universitas Katolik Indonesia Atma Jaya Jakarta, 2016)
The article describes and analyzes the principle of good faith in the industrial relation system with positive values that make social dialogue as alternative solution of the dispute settlement in industrial relations system. Its also describes the efforts at the HERO Supermarket by the management and the union utilizing social dialogues the basis of the principle of good faith, which resulted in social partnership among the management, the union and other parties. It is an interesting example of how the parties developed awareness of the essence of social dialogue as an alternative way particularly in industrialrelations dispute settlement mechanism.